Sidang Keliling Dalam Perceraian (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
In Aceh Province, the Religious Court is called the Sharia Court, each district or city has its own Sharia Court office which is located in the district or city. As stated in Law Number 3 of 2006 concerning amendments to Law Number 7 of 1989 concerning Religious Courts that: "The Religious Court is located in the capital of the district or city and its jurisdiction covers the district or city area. This research is based on field research. The purpose of field research is to intensively study the background of the current situation and the interaction of the environment of a social unit; individual, group, institution or community. The results of the study are that community participation in the implementation of the circuit court in divorce cases at the Tapaktuan Sharia Court is very high, there are even several special requests from the community for the implementation of the circuit court for several cases, especially divorce cases and the influence of the circuit court in the social life of the community is the emergence of awareness for the community that the termination of a marriage relationship is very important to obtain legal certainty.